Serum galectin-3BP as a novel marker of obesity and metabolic syndrome in Chinese adolescents - Zhongyi Zhao; Deliang Wen; Shihan Zhen; Yanan Ma; Yanshuo Han (BMJ Open Diabetes Research & Care)
Introduction Childhood obesity (OB) and metabolic syndrome (MetS) have become a worldwide health problem. Comparative proteomic approaches are widely used in human OB to analyze protein changes in blood plasma. The present study determined the galectin-3 binding protein (galectin-3BP) expression level in different weight categories and assessed the associations between galectin-3BP and OB and MetS.Research design and methods The current study included 932 Chinese adolescents 13–18 years of age. The biochemical and anthropometric variables of all the subjects were evaluated using standardized procedures. The differentially expressed proteins (DEPs) were investigated among 60 adolescents (20 normal weight, 20 overweight and 20 obese) using tandem mass tag (TMT) quantitative proteomics. The serum galectin-3BP level was measured using ELISA. The associations between galectin-3BP and OB and MetS were analyzed in 932 adolescents using multiple logistic regression analyses.Results A significant DEP, galectin-3BP, can effectively separate the obese from the normal weight group using TMT. Adolescents in tertile 3 of galectin-3BP, when compared with adolescents in the tertile 1, were positively associated with OB (OR=3.32, 95% CI 1.79 to 6.16) and MetS (OR=3.28, 95% CI 1.30 to 8.26). The receiver operating characteristic curve for galectin-3BP in subjects with MetS indicated that the area under the curve was 0.85 (95% CI 0.79 to 0.91).Conclusions This study confirmed an association between galectin-3BP and OB in Chinese adolescents, and galectin-3BP was also positively associated with MetS, and thus might be useful for identifying adolescents with MetS.